2021
DOI: 10.1007/s10853-021-05797-2
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylonitrile modified partially reduced graphene oxide composites for the extraction of Hg(II) ions from polluted water

Abstract: Polyacrylonitrile nanoparticles grafted on ethylene diamine functionalized partially reduced graphene oxide (PAN-PRGO) was prepared via in situ emulsion polymerization and was further modified to contain amidoxime, amdinoethylene diamine, and carboxylic groups on the surface of the graphene nanosheets via partial hydrolysis of the nitrile groups on the polymer chains of the composite using (4% NaOH, 20 min) (HPAN-PRGO). The properties and morphologies of the prepared composites were compared through FTIR, UV-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…The high-resolution C 1s spectrum (Figure S2A) attributed to the OAC was deconvoluted to four peaks with binding energies at 289.3 eV (C in COOH), 287.5 eV (C in CO), 285.9 eV (C in C–O), and 284.9 eV (C in C–C, CC). , Deconvolution of the C 1s spectrum of MT-MAC showed in Figure S2B identifies four peaks with binding energies at 288.6, 287.1, 286.3, and 284.6 eV corresponding to C–NH 2 , CN/N–CO, C–O/C–S, and C–C/CC, respectively. ,,, Consequently, the chemical modification of OAC with MT was also evident from the peaks at 286.3, 287.2, and 288.6 eV for (C–S, C–N), (N–CO, CN), and C-NH 2 , respectively. The high-resolution O 1s of OAC (Figure S2C) was deconvoluted to three peaks with binding energies at 531.5 eV (O in O–H), 532.5 eV (O in CO), and 533.9 eV (O in COOH), while the O 1s spectrum of MT-MAC is deconvoluted to two peaks with binding energies at 531.2 eV (O in H–N–CO) and 533.1 eV (O in CO). ,,, The successful incorporation of melamine thiourea onto the surface of OAC is also approved by the S 2p and N 1s spectra represented in Figure S2F,E, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high-resolution C 1s spectrum (Figure S2A) attributed to the OAC was deconvoluted to four peaks with binding energies at 289.3 eV (C in COOH), 287.5 eV (C in CO), 285.9 eV (C in C–O), and 284.9 eV (C in C–C, CC). , Deconvolution of the C 1s spectrum of MT-MAC showed in Figure S2B identifies four peaks with binding energies at 288.6, 287.1, 286.3, and 284.6 eV corresponding to C–NH 2 , CN/N–CO, C–O/C–S, and C–C/CC, respectively. ,,, Consequently, the chemical modification of OAC with MT was also evident from the peaks at 286.3, 287.2, and 288.6 eV for (C–S, C–N), (N–CO, CN), and C-NH 2 , respectively. The high-resolution O 1s of OAC (Figure S2C) was deconvoluted to three peaks with binding energies at 531.5 eV (O in O–H), 532.5 eV (O in CO), and 533.9 eV (O in COOH), while the O 1s spectrum of MT-MAC is deconvoluted to two peaks with binding energies at 531.2 eV (O in H–N–CO) and 533.1 eV (O in CO). ,,, The successful incorporation of melamine thiourea onto the surface of OAC is also approved by the S 2p and N 1s spectra represented in Figure S2F,E, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The constant b is used in the calculation of the R L value as shown in eq . Equation can be used to predict whether the shape of the isotherm will be irreversible ( R L = 0), linear ( R L = 1), negative ( R L > 1), or positive (0 < R L < 1). , The linear form of the Freundlich isotherm model, which is based on the assumption multilayer adsorption occurring on heterogeneous surfaces, is as follows , where k F and 1/ n represent the Freundlich constant and adsorption density, respectively, and can be calculated from the intercept and slope of the linear graph shown in Figure S4A. The parameters of both models were calculated and are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum adsorption occurred at 120 min. This is because the surface area of the graft copolymer is very large, carrying a large number of adsorption active sites [34]. As the adsorption process proceeds, the vacant active sites are gradually occupied.…”
Section: Effect Of Contact Time On the Adsorption Of Hg(ii) Ions By The Graft Polymermentioning
confidence: 99%
“…Moreover, GO has an abundance of oxygen-containing functional groups (i.e., carboxylic acids, epoxides, and alcohols) that play a significant role in modifying the structure and surface of GO . The functional groups can act as active sites to store Na ions and also increase the d -spacing of the GO nanosheets to provide wider pores to enable Na ion transport since the size of Na ions is 25.5% larger than that of Li ions. Yildirim et al and Coskun et al have reported the synthesis of graphene oxide that can be linked together to form a new layered structure with the expansion of the interlayer distance without filling the space between them. For instance, Zhao et al cross-linked GO nanosheets using porphyrin to enable a d -spacing of ∼7.67 Å between the GO layers, contributing to a specific capacity of 200 mA g –1 at a current density of 100 mA g –1 up to the 20th cycle . Li et al sandwiched nano-Fe 2 O 3 between GO nanosheets, which increased the d -spacing between GO layers and gave a specific capacity of 420 mAh g –1 after 100 cycles at 0.1C .…”
Section: Introductionmentioning
confidence: 99%